SURABAYA SEBAGAI KOTA MARITIM : STRATEGI PEMASARAN CITY BRANDING DAN TANTANGAN DI MASA DEPAN - Febrina Hambalah (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2017)
In today's digital era, each city is competing with another city. Each city features uniqueness that can be highlighted from him, all of it is to attract funding from investors. The ultimate goal is to improve the welfare of the city. Surabaya has been known by the people of Indonesia through the history of Indonesian independence as The City of Heroes. However, the identity as The City of Heroes is not yet strong enough to attract investment and the interest of tourists to invest in this city of Surabaya. Thus a new identity, in this case new branding must be made in order to strengthen the position of Surabaya before the eyes of the community both internal communities within the city of Surabaya, as well as external communities outside the city of Surabaya and abroad. The research method that was used is descriptive qualitative method. This method is by doing observation and analysis of marketing strategy of city branding which have been done by Surabaya city. This scientific work was developed by using literature review approach or literature study. In this research noted that the process of building a city brand is not easy. Especially if the parties involved have a political interest in it. As a social construct, city branding of the city of Surabaya as a city of Maritime will certainly generate various responses from the community. The response can be a positive response, as well as a negative response.